Greek Alchemy from Late Antiquity to Early Modernity - Nicolaïdis, Efthymios (Brepols, 2018)
What do we really know about Greek alchemy throughout the ages? Certain periods, such as the Byzantine and post-Byzantine, have been somewhat overlooked. This volume engages in the the effort to shed light on certain aspects of Greek Alchemy from the 1<span class=